Why do retail customers hesitate for shopping grocery online? - Klepek, Martin; Bauerová, Radka (Technological and Economic Development of Economy, 2020)
Considering a relatively slow adoption of online grocery shopping in the vast majority of the world markets, the main objective of this study was to uncover any new reasons why customers hesitate to shop groceries online. Moreover, we were not looking for undiscovered discouraging reasons only but also intended to validate previously researched reasons in published studies. Thus, we have first used a systematic literature review to cover all relevant previous studies on online grocery non-buyers. Even though this process is time-consuming, it provides a coherent overview of the published material on the topic. Further, we designed a web-based survey of 670 respondents from the general internet population. The data in open-ended questions related to online grocery attitudes and opinions were analysed by the content analysis. 14 thematic units emerged from the process from which the majority confirmed previously researched negative attitudes toward online grocery shopping. Non-buyers prefer to see grocery in person before buying it, there is a distrust in e-tailers to choose the best and freshest grocery, non-buyers prefer personal contact with the seller and behave habitually. Moreover, they tend to shop offline also because of hedonic reasons and pleasure from the shopping experience. Novel reasons why people hesitate to shop online in this category were the time consumption where consumers perceived online shopping slow regarding order-delivery time gap and were reluctant to pay for the delivery service, to mention just a few. We conclude with a summary of our results and a handful of recommendation for e-tail companies.